Exploring the Chemical Profiles and Biological Values of Two Spondias Species (S. dulcis and S. mombin): Valuable Sources of Bioactive Natural Products - Kouadio Ibrahime Sinan; Gokhan Zengin; Dimitrina Zheleva-Dimitrova; Reneta Gevrenova; Marie Carene Nancy Picot-Allain; Stefano Dall'Acqua; Tapan Behl; Bey Hing Goh; Patrick Tang Siah Ying; Mohamad Fawzi Mahomoodally (MDPI AG, 2021)
Spondias species have been used in traditional medicine for different human ailments. In this study, the effect of different solvents (ethyl acetate, methanol, and water) and extraction methods (infusion, maceration, and Soxhlet extraction) on the enzyme inhibitory activity against acetylcholinesterase, butyrylcholinesterase, tyrosinase, α-amylase, α-glucosidase, and antioxidant properties of S. mombin and S. dulcis leaves and stem bark were evaluated. Ultra-high-performance liquid chromatography-high resolution mass spectrometry (UHPLC-HRMS) yield in the identification and/or annotation of 98 compounds showing that the main secondary metabolites of the plant are gallic and ellagic acids and their derivatives, ellagitannins, hydroxybenzoic, hydroxycinnamic, acylquinic acids and flavonols, flavanones, and flavanonols. The leaves infusion of both Spondias species showed highest inhibition against acetylcholinesterase (AChE) (10.10 and 10.45 mg galantamine equivalent (GALAE)/g, for S. dulcis and S. mombin, respectively). The ethyl acetate extracts of the stem bark of S. mombin and S. dulcis actively inhibited α-glucosidase. Methanolic extracts of the leaves and stem bark exhibited highest tyrosinase inhibitory action. Antioxidant activity and higher levels of phenolics were observed for the methanolic extracts of Spondias. The results suggested that the Spondias species could be considered as natural phyto-therapeutic agents in medicinal and cosmeceutical applications.